Thyroid Ultrasound-Guided Fine-Needle Aspiration Cytology Results: Observed Increase in Indeterminate Rate over the Past Decade. (April 2017) - Manning, Amy M.; Yang, Huaitao; Falciglia, Mercedes; Mark, Jonathan R.; Steward, David L.
Objectives: To evaluate changes in distribution of reported thyroid nodule fine-needle aspiration (FNA) cytopathology results since implementation of the Bethesda classification and revised 2015 American Thyroid Association (ATA) guidelines for selecting nodules for biopsy. Study Design: Retrospective review. Setting: Tertiary academic medical center. Subjects and Methods: Evaluation of ultrasound (US)–guided thyroid FNA by a single surgeon using 2015 ATA nodule selection criteria and Bethesda reporting on 211 thyroid nodules in a 1-year period (2015). Comparison is made to an earlier sample wherein any nodule >1 cm underwent US FNA with cytology reported prior to Bethesda consensus (2006). Results: The current cohort involved mostly women (79%); nodules ranged from 1 to 7 cm (mean ± SEM, 2.4 ± 0.07 cm). Mean ± SEM age was 53.5 ± 1.1 years. Bethesda reporting yielded 6% nondiagnostic, 57% benign, 3% malignant, and 34% indeterminate (27% atypia of undetermined significance [AUS]/follicular lesion of undetermined significance [FLUS], 4% follicular neoplasm [FN]/Hürthle neoplasm [HN], and 2% suspicious for malignancy [SFM]). The malignancy rate in indeterminate nodules was 26% (18% AUS/FLUS, 33% FN/HN, and 80% SFM). Age, sex, or nodule size did not correlate with indeterminate cytology. The comparator sample of 447 nodules had significantly different distribution, with 7% nondiagnostic, 80% benign, 5% malignant, and 8% indeterminate ( P < .00001). Conclusion: We observed a significantly increased proportion of indeterminate cytology and corresponding decrease in benign nodules compared with an earlier sample, predominately from an increase in AUS/FLUS. Multiple factors are likely involved, including selection of sonographically suspicious nodules for biopsy based upon 2015 ATA guidelines coupled with cytopathological interpretation by a new generation of cytopathologists trained in the era of Bethesda reporting; further study is required to make a definitive conclusion.